Attempt of Costus arbuscular mycorrhizal inoculants association with leguminous foliage whey on chlorophyll of sunflower (Helianthus annus L.) plants: Comparative influence of leafy whey and mycorrhiza on Helianthus growth. - Jadhav, Rajesh Khanduji; Anil, Lodhi (Journal of Plant Stress Physiology, 2020)
Reporters founded that mycorrhizal association in plant kingdom improves the plant growth. The present attempt has been on the use of Mycorrhiza for Helianthus growth in stress condition of the adverse red soil of konkan region, India and other climatic factors. Earlier reporters for the purpose to avoid chemical fertilisers, founded that Deproteinised juice (DPJ) or foliage whey induces appropriate plant growth and enhance soil fertility. During present investigation, mycorrhiza from Costus sp application to soil of potted sunflower plants influence was compared with organic DPJ addition obtained from fenugreek foliage during the process of green crop fractionation (GCF) technique. This whey is randomly disposed during this technology of leaf protein preparation, so appropriate use of it is advised. Whether the mycorrhiza and DPJ combination treatment were feasible for seed germination and the seedling growth of the Helianthus plant, it was analysed and compared with control. Studies were experimented on the effect of mycorrhiza treated alone and DPJ treated alone whether improves the plant growth. DPJ if added with mycorrhiza in soil, showed significant rate of germination. In earlier research, it was elucidated that the DPJ contains phytohormones auxins, gibberellins and cytokinins in unknown quantity which boosts the plant growth comparative to mycorrhizal influence. The chlorophyll content of the DPJ treated plants enhanced as compared with control while the content showed no significant difference with mycorrhiza.